Pengaruh Kualitas Sistem Informasi Akuntansi Manajemen, Desentralisasi, Ketidakpastian Lingkungan terhadap Kinerja Manajerial pada Perusahaan Perkebunan PT PD Paja Pinang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the impact of the quality of Management Accounting Information Systems (MAIS), decentralization, and environmental uncertainty on managerial performance. There were 30 employees with managerial responsibilities selected as respondents using saturated sampling techniques. Data collection was conducted through questionnaires, then analyzed using descriptive statistical analysis, validity testing, reliability testing, classical assumption testing, and multiple linear regression supported by SPSS software version 29. The findings of this study indicate that decentralization has a positive and significant impact on managerial performance, while the quality of SIAM and environmental uncertainty do not appear to have a significant impact. The insignificance of the SIAM variable is thought to be due to low system integration and user limitations in utilizing the application. On the other hand, environmental uncertainty has not been considered a strategic factor in the decision-making process. Therefore, the findings of this study emphasize the importance of implementing decentralization to improve managerial effectiveness, as well as the need to strengthen information systems and monitor environmental conditions within organizations.